LEGAL RESPONSIBILITY AND ISLAMIC ECONOMIC PERSPECTIVE IN THE USE OF BLOCKCHAIN TECHNOLOGY IN INDONESIA - Ahmad Sodiq; Muhammad David Marukhan; Aulia Zahnabila; Alika Fitria Salmarani (STMIK Indonesia Banda Aceh, 2026)
The development of blockchain brings efficiency, transparency, and security to transactions, but at the same time raises the issue of attribution of responsibility when there are smart contract errors, data leaks, system failures, or user losses. This study uses normative legal methods through legislative, conceptual, and Islamic law approaches with primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that legal responsibility in the blockchain ecosystem cannot be centered on one party, but rather needs to be divided proportionally according to the level of control and risk contribution of each legal subject. Developers are responsible for code security, system design, and smart contract reliability. The platform assumes obligations for service governance, consumer protection, and data security. Users remain responsible for the legitimate and secure use of the technology. In the perspective of Islamic economic law, the principles of amanah, dhaman, and maslahah affirm the importance of accountability, justice, and usefulness in the use of blockchain. This research emphasizes the need to harmonize national regulations and sharia values so that the blockchain ecosystem develops responsibly, adaptively, and protects the interests of the parties. The findings also show that an adaptive legal framework is needed to prevent norm vacuums and clarify recovery mechanisms when losses occur.